Infliximab for treatment of resistant pyoderma gangrenosum associated with Crohn's disease - Ferkolj, Ivan (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2006)
We present the case of an 18-year-old woman with Crohnćs disease manifested bydiffuse abdominal pain, bloody diarrhea accompanied by arthralgia, and swelling of large joints. On the lateral aspect of her right ankle there was an hemorrhagic, necrotic bullous lesion measuring 3 x 4 cm, surrounded by cutaneous inflammation and erythema. Biopsy showed a neutrophilic abscess-likeulcerative skin inflammation, which was diagnosed as pyoderma gangrenosum. The patient was treated with high doses of parenteral methylprednisolone, but her condition failed to improve and infliximab, a TNF-alpha blocking agent, was instituted. An immediate response of Crohnćs disease was observed and, over the next 5 weeks, the ulcer on her right ankle also healed completely.